Formation of future specialists technical competence in woodworking technological and professional education - Kovalenko, Ihor (Professional Pedagogics, 2017)
Requirements and tasks of educational areas “Technology” and “Professional education” born by the modern phase of education activity concerning training of future woodworking specialists are analyzed in the article. Latest investigations devoted to the foundation and experimental tests of students’ readiness to the pedagogical activity efficiency criteria are evaluated. It is shown that no investigations have been performed before to formulate the criteria of technical competence of future woodworking teachers by means of information and communication technologies (ICT).Modeling as one of the main scientific knowledge categories and world study method has been considered. The essence of pedagogical model and the professional-pedagogical structure content have been revealed. Readiness for the professional activity of future teachers of technology and pedagogues of woodworking technological training as a holistic personality formation that allows to organize successfully the creative activity of the students, where such activity is targeted on their moral values and creative capability. Structure-functional model of technical competence formation system of future woodworking pedagogues (using ICT) is theoretically based and constructed. Examples of effective learning using ICT are presented.According to the author, combination of ICT with such pedagogical technologies as free education and self-development make possible for the future woodworking technology teachers and pedagogues of professional education to assimilate maximum of the learning material, and that will make the positive affect on the quality of the student’s training and on their readiness to the professional activity.
Keywords: pedagogical model; structure of the professionalpedagogical activity; components and features; tasks; stages; didactic environment